Irisin activates Opa1-induced mitophagy to protect cardiomyocytes against apoptosis following myocardial infarction - Xin, Ting (Aging (Albany NY), 2020)
Myocardial infarction is characterized by sudden ischemia and cardiomyocyte death. Mitochondria have critical roles in regulating cardiomyocyte viability and can sustain damage under ischemic conditions. Mitophagy is a mechanism by which damaged mitochondria are removed by autophagy to maintain mitochondrial structure and function. We investigated the role of the dynamin-like GTPase optic atrophy 1 (Opa1) in mitophagy following myocardial infarction. Opa1 expression was downregulated in infarcted hearts in vivo and in hypoxia-treated cardiomyocytes in vitro. We found that Opa1 overexpression protected cardiomyocytes against hypoxia-induced damage and enhanced cell viability by inducing mitophagy. Opa1-induced mitophagy was activated by treatment with irisin, which protected cardiomyocytes from further damage following myocardial infarction. Opa1 knockdown abolished the cardioprotective effects of irisin resulting in an enhanced inflammatory response, increased oxidative stress, and mitochondrial dysfunction in cardiomyocytes. Our data indicate that Opa1 plays an important role in maintaining cardiomyocyte viability and mitochondrial function following myocardial infarction by inducing mitophagy. Irisin can activate Opa1-induced mitophagy and protect against cardiomyocyte injury following myocardial infarction.